Is there IgA of gut mucosal origin in the serum of HIV1 infected patients?. Issue 6 (June 1994) - Quesnel, A; Moja, P; Lucht, F; Touraine, J L; Pozzetto, B; Genin, C
Abstract : This study was performed in 77 HIV1 seropositive adult patients to characterise the IgA hyperglobulinaemia seen in the serum during the course of HIV infection. It was shown that both IgA1 and IgA2 subclass concentrations were simultaneously increased but the IgA1 increase was predominant. Secretory IgA (SIgA) concentration was significantly increased and IgA activity to gliadin, bovine serum albumin, and casein could be detected and was correlated with SIgA concentration. In contrast, IgA activity to cytomegalovirus and to tetanus toxoid did not correlate with total IgA concentration. These data suggest the presence of IgA from gut mucosal origin in the serum of these patients. Hyper IgA was inversely correlated with the CD4+ cell number. The increase of all parameters studied varied according to the total IgA concentration in the serum but was also directly related to the stage of immune deficiency in patients with hyper IgA.